2023
DOI: 10.1021/acsnano.3c06084
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning Terahertz Single-Cell Metabolic Viability Study

Ning Yang,
Qian Shi,
Mingji Wei
et al.

Abstract: Cell viability assessment is critical, yet existing assessments are not accurate enough. We report a cell viability evaluation method based on the metabolic ability of a single cell. Without culture medium, we measured the absorption of cells to terahertz laser beams, which could target a single cell. The cell viability was assessed with a convolution neural classification network based on cell morphology. We established a cell viability assessment model based on the THz-AS (terahertz-absorption spectrum) resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…Machine learning has greatly advanced biomedical research. A flowchart of the machine-learning process is shown in Figure d. PCA is used to process spectral data with high dimensions, and by calculating the covariance matrix of spectral data, the correlation between different wavelength points can be analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning has greatly advanced biomedical research. A flowchart of the machine-learning process is shown in Figure d. PCA is used to process spectral data with high dimensions, and by calculating the covariance matrix of spectral data, the correlation between different wavelength points can be analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, researchers have observed that necrosis is associated with activation of signaling pathways and can be inhibited by specific enzymes. These findings challenge the conventional understanding of uncontrolled necrosis, leading to new investigations of necrotic mechanisms and functioning . Cell death is not only regulated by biological signals but also closely associated with changes in biophysical properties in cell. ,, For example, in apoptotic cells, intracellular transport is accelerated at an early stage as a result of elevated adenosine 5′-triphosphate (ATP) levels, while intranuclear diffusion is reduced in the execution stage due to nuclear condensation . In necrotic cells, structural changes including cell swelling, cellular lysis, and plasma membrane rupture would also significantly impact the intracellular environment and dynamics, collectively coordinating the progress of necrosis. However, the spatiotemporal characteristics of the physical properties within cells undergoing necrosis remain unclear, limiting our understanding of the principle of necrosis.…”
Section: Introductionmentioning
confidence: 99%